2017
DOI: 10.2514/1.t5009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Combustion Properties of Energetic Thin Films with Carbon Nanotubes

Abstract: The effect of varying carbon nanotube concentration on ignition delay, flame speed, and electrical and thermal conductivity of three-dimensional printable energetic thin films made of magnesium and manganese oxide was investigated. Polyvinylidene fluoride was used as the binder for depositing the stoichiometric Mg∕MnO 2 mixture into thin films with an average thickness of 200 μm using an extrusion-based blade-casting method. Four films with a 0, 0.5, 1.0, and 1.5 wt % carbon nanotube were prepared. The ignitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…As the energy release rate is directly dependent on the equivalence ratio, size and morphology of the oxidizer and fuel, many research studies propose to manipulate the material formulation; however it requires expensive and time-consuming synthesis and characterization loops. Another empirical procedure reported in the literature consists in doping the energetic composite with additives featuring high thermal diffusivities like metals and carbon structures [19][20][21][22][23] to enhance the heat conduction in different areas of the energetic composite with the goal to accelerate the thermal front (flame) propagation. In [19] the authors show that inclusions of 1.5 wt% carbon nanotubes in the Mg/MnO 2 /polyvinylidene fluoride (PVDF) films improved the burn rate by a factor of 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the energy release rate is directly dependent on the equivalence ratio, size and morphology of the oxidizer and fuel, many research studies propose to manipulate the material formulation; however it requires expensive and time-consuming synthesis and characterization loops. Another empirical procedure reported in the literature consists in doping the energetic composite with additives featuring high thermal diffusivities like metals and carbon structures [19][20][21][22][23] to enhance the heat conduction in different areas of the energetic composite with the goal to accelerate the thermal front (flame) propagation. In [19] the authors show that inclusions of 1.5 wt% carbon nanotubes in the Mg/MnO 2 /polyvinylidene fluoride (PVDF) films improved the burn rate by a factor of 4.…”
Section: Introductionmentioning
confidence: 99%
“…Another empirical procedure reported in the literature consists in doping the energetic composite with additives featuring high thermal diffusivities like metals and carbon structures [19][20][21][22][23] to enhance the heat conduction in different areas of the energetic composite with the goal to accelerate the thermal front (flame) propagation. In [19] the authors show that inclusions of 1.5 wt% carbon nanotubes in the Mg/MnO 2 /polyvinylidene fluoride (PVDF) films improved the burn rate by a factor of 4. Recently, Julien et al showed that incorporation of gold nanoparticles into Al/CuO nanothermite increases the ignitability and enhances burning properties [24].…”
Section: Introductionmentioning
confidence: 99%